2022
DOI: 10.3389/fnagi.2022.1010548
|View full text |Cite
|
Sign up to set email alerts
|

Association of retinal thickness and microvasculature with cognitive performance and brain volumes in elderly adults

Abstract: BackgroundRetinal structural and microvascular changes can be visualized and have been linked with cognitive decline and brain changes in cerebral age-related disorders. We investigated the association between retinal structural and microvascular changes with cognitive performance and brain volumes in elderly adults.Materials and methodsAll participants underwent magnetic resonance imaging (MRI), and a battery of neuropsychological examinations. Macula retinal thicknesses (retinal nerve fiber layer, mRNFL, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…5B and S58-S72 ). Several studies have reported that retinal layer thickness may be a prognostic biomarker of cognitive impairment and long-term cognitive decline in older individuals 84, 85 . Retinal imaging traits were in LD ( r 2 ≥ 0.6) with multiple neurodegenerative disorders, such as in 2q24.3, 17q21.31, 8p23.1, and 15q12 with Parkinson’s disease 86 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5B and S58-S72 ). Several studies have reported that retinal layer thickness may be a prognostic biomarker of cognitive impairment and long-term cognitive decline in older individuals 84, 85 . Retinal imaging traits were in LD ( r 2 ≥ 0.6) with multiple neurodegenerative disorders, such as in 2q24.3, 17q21.31, 8p23.1, and 15q12 with Parkinson’s disease 86 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thinning of the RNFL and GCIPL is not only regarded as a ‘neurodegeneration phenomenon’ but also has been suggested as a useful indicator for monitoring the disease progression. Retinal sublayers decrease has been correlated with older age 36 and incidence of certain disease 37 . The deterioration of the GCIPL and preservation of the RNFL in thalamic stroke patients may indicate possible subtle deterioration of the dendritic complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal sublayers decrease has been correlated with older age 36 and incidence of certain disease. 37 The deterioration of the GCIPL and preservation of the RNFL in thalamic stroke patients may indicate possible subtle deterioration of the dendritic complexity. The faster thinning of GCIPL in thalamic infarction patients might be noted to be an early onset and continuous neurodegeneration progression, even if there is an improvement in their neurological deficit (as measured by NIHSS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other exclusion criteria included relevant opacities of the optic media. The inclusion and exclusion criteria of our study participants are well described in our previous studies ( Tao et al, 2022 ; Wang et al, 2022 ). The Ethics Committee of West China Hospital of Sichuan University, China, approved the study protocol (No.…”
Section: Methodsmentioning
confidence: 99%